A study on interrupted clopidogrel refill and the impact after discharged from Hospital Tengku Ampuan Rahimah, Klang / Nur Syellawaty Ahmad - Ahmad, Nur Syellawaty (2017)
Acute Coronary Syndrome is a chronic disease which requires immediate and long term treatment. Thus, there are many challenges in sustaining the continuity of the treatment especially when patients are discharged from hospital to primary care. Several factors that interrupt the sustainability and continuity of the treatment have been identified. One of the factors that cause disrupted treatment includes interruption in getting the medication. In Malaysia, there are limited local studies on the continuity of Clopidogrel treatment at the primary care. This study aims to find the frequency of interrupted refill of Clopidogrel in primary care and its implications. This was a retrospective study involving 115 ACS patients who were discharged from the hospital between January 1, 2014 and December 31, 2015 to the primary care. Out of 115 patients, 75(65.2%) patients were male, 40(34.8%) patients were female with age ranging between 31 to 80 years old. The distribution of ethnicity includes all the major races in Malaysia. There were 54(47.0%) Malay patients, 39(33.9%) Indian patients and 22(19.1%) Chinese patients. It was found that most of the patients (N=89, 77.39%) did not comply and had interrupted Clopidogrel refill prescriptions and only 22.6% of patients (N= 26) complied and refilled their prescriptions monthly without fail. No variables are significantly associated to the interrupted refill. The implication of interrupted Clopidogrel refill was found to be associated with the increased risk of re-admission due to Myocardial infarction (OR 10.25; 95% CI 2.28 – 46.00; p<0.005). In a healthcare system that is being funded by the government, there should be no reasons for interrupted refill especially in chronic diseases. There is a need to identify best approaches to improve or optimize prescriptions filling after patients were discharged from hospital.